Does ageism affect the management of ischaemic heart disease? - Bond, M; Bowling, A; McKee, D; Kennelly, M; Banning, A; Dudley, N; Elder, A; Martin, A (2003)
OBJECTIVES: To analyse access by age to exercise testing, coronary angiography, revascularisation (percutaneous transluminal coronary angioplasty/stent insertion and coronary artery bypass graft surgery) and receipt of thrombolysis, where indicated, for hospital patients with diagnosed cardiovascular disease. METHOD: Retrospective case note analysis, tracking each case backwards and forwards by 12 months from the patient's date of entry to the study. The setting was a district hospital in the eastern part of outer London. The case notes eligible for inclusion were those of elective and emergency in-patients with an in-patient ICD-10 code of ischaemic heart disease, angina pectoris or acute myocardial infarction and a consecutive 20% sample of new cardiac outpatients with these diagnoses. RESULTS: Analysis of 712 case notes showed that older hospital patients with ischaemic heart disease, and with indications for further investigation, were less likely than younger people to be referred for exercise tolerance tests and cardiac catheterisation and angiography. This was independent of both gender and severity of condition. Older patients did not appear to be discriminated against in relation to receipt of indicated treatments (revascularisation or thrombolysis), although, in the case of revascularisation, older patients were more likely to have been filtered out at the investigation stage (catheterisation and angiography), so selection bias partly explains this finding. CONCLUSIONS: The current findings from a single hospital are comparable with the results from a broader study of equity of access by age to cardiological interventions in another district hospital in the same region. Although only two hospitals were analysed, the similarity of findings enhances the generalisability of the results presented here. It appears that age per se causes older cardiac hospital patients to be treated differently.